Pandora hearts. 16 - Mochizuki, Jun (Yen Press, 2013)
"Oz. Leo. Inescapable tragey assaults and binds the two. He is no more. That simple truth tears their hearts apart like casltes of sand caving in...But will history repeat itself when, in the midst of their sorrow, the two are pitted against each other in a struggle that could end in catastrophe?"